1999
DOI: 10.1038/11732
|View full text |Cite|
|
Sign up to set email alerts
|

Determining the influence of structure on hybridization using oligonucleotide arrays

Abstract: We have studied the effects of structure on nucleic acid heteroduplex formation by analyzing hybridization of tRNAphe to a complete set of complementary oligonucleotides, ranging from single nucleotides to dodecanucleotides. The analysis points to features in tRNA that determine heteroduplex yield. All heteroduplexes that give high yield include both double-stranded stems as well as single-stranded regions. Bases in the single-stranded regions are stacked onto the stems, and heteroduplexes terminate at potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
113
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(122 citation statements)
references
References 54 publications
9
113
0
Order By: Relevance
“…We have described a method to identify RNA sites that are favorable for hybridization with random oligonucleotide libraries and extension by reverse transcriptase, and have called them extendible sites+ The first question to ask is what is the relationship between extendible sites and RNA accessible sites described in the literature+ Accessible sites are loosely defined as those regions on an RNA molecule that can form stable complexes with complementary oligonucleotides+ However, conditions under which this stability is achieved as well as the length of the oligonucleotides used for analysis can significantly vary in different methods+ In one of the first methods (Hogenauer, 1970;Lewis & Doty, 1970;Uhlenbeck et al+, 1970;Uhlenbeck, 1972), RNA accessible regions were identified by using equilibrium dialysis to measure the association constants for the hybridization of 3-and 4-mer oligoribonucleotides to complementary regions of tRNA+ The tri-and tetranucleotides used in these studies are possibly the shortest oligonucleotides that can be employed for RNA probing, because 3-4 nt is the minimal size of a stable duplex corresponding to a nucleation complex (Craig et al+, 1971;Porschke & Eigen, 1971)+ Therefore, very short oligonucleotides bind to RNA regions that are not only in a single-stranded conformation, but are also flexible enough to adopt a duplex conformation upon binding (Uhlenbeck et al+, 1970)+ On the other side of the length spectrum, hybridization with arrays of oligonucleotides (Milner et al+, 1997;Mir & Southern, 1999;Sohail et al+, 1999) generally employs much longer probes+ Although the method can analyze oligonucleotides ranging from 1 to 21 nt, optimal binding is usually achieved with 12-to 17-mers+ Because accessible regions of such length do not likely appear frequently in RNA structures, the assumption is that long oligonucleotides initiate binding at short regions that are sterically accessible for nucleation, and the heteroduplex subsequently propagates into more structured RNA regions+ Kinetic restrictions on the perturbations of RNA secondary structure at the oligonucleotide binding site may explain the long hybridization times (3-18 h) used in this method+…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have described a method to identify RNA sites that are favorable for hybridization with random oligonucleotide libraries and extension by reverse transcriptase, and have called them extendible sites+ The first question to ask is what is the relationship between extendible sites and RNA accessible sites described in the literature+ Accessible sites are loosely defined as those regions on an RNA molecule that can form stable complexes with complementary oligonucleotides+ However, conditions under which this stability is achieved as well as the length of the oligonucleotides used for analysis can significantly vary in different methods+ In one of the first methods (Hogenauer, 1970;Lewis & Doty, 1970;Uhlenbeck et al+, 1970;Uhlenbeck, 1972), RNA accessible regions were identified by using equilibrium dialysis to measure the association constants for the hybridization of 3-and 4-mer oligoribonucleotides to complementary regions of tRNA+ The tri-and tetranucleotides used in these studies are possibly the shortest oligonucleotides that can be employed for RNA probing, because 3-4 nt is the minimal size of a stable duplex corresponding to a nucleation complex (Craig et al+, 1971;Porschke & Eigen, 1971)+ Therefore, very short oligonucleotides bind to RNA regions that are not only in a single-stranded conformation, but are also flexible enough to adopt a duplex conformation upon binding (Uhlenbeck et al+, 1970)+ On the other side of the length spectrum, hybridization with arrays of oligonucleotides (Milner et al+, 1997;Mir & Southern, 1999;Sohail et al+, 1999) generally employs much longer probes+ Although the method can analyze oligonucleotides ranging from 1 to 21 nt, optimal binding is usually achieved with 12-to 17-mers+ Because accessible regions of such length do not likely appear frequently in RNA structures, the assumption is that long oligonucleotides initiate binding at short regions that are sterically accessible for nucleation, and the heteroduplex subsequently propagates into more structured RNA regions+ Kinetic restrictions on the perturbations of RNA secondary structure at the oligonucleotide binding site may explain the long hybridization times (3-18 h) used in this method+…”
Section: Discussionmentioning
confidence: 99%
“…Targeting RNA molecules with sequence-specific oligonucleotides is an important step in antisensemediated gene suppression and in various methods of RNA analysis, such as primer extension, RT-PCR, and the RNA invasive cleavage reaction (Kwiatkowski et al+, 1999)+ The major problem with probe design for such RNA assays is that the rich secondary and tertiary structures of RNA molecules leave only a small fraction of RNA sequences available for efficient oligonucleotide hybridization (Lewis & Doty, 1970;Uhlenbeck et al+, 1970;Lima et al+, 1992;Vickers et al+, 2000)+ As a consequence, random selection of oligonucleotides for a given RNA target without prior knowledge of the accessible regions on the molecule has been proven an ineffective approach+ It is estimated that randomly targeting RNA with antisense oligonucleotides yields only one oligonucleotide showing significant inhibition of gene expression out of every 18-20 tested (Monia et al+, 1992;Dean et al+, 1994;Matveeva et al+, 1998;Stein, 1999)+ To address this problem, several experimental and theoretical approaches have been developed for identifying accessible regions in RNA+ The RNA accessible sites mapping using hybridization with oligonucleotide libraries followed by RNase H cleavage has been shown to significantly increase the odds of designing effective antisense oligonucleotides compared with the random "walking" method (Ho et al+, 1996(Ho et al+, , 1998Birikh et al+, 1997;Matveeva et al+, 1997)+ However, several factors complicate the application of RNase H assay and the similar method employing ribozyme libraries with random internal guide sequences (Campbell & Cech, 1995;Lieber & Strauss, 1995)+ The most critical of these are background signal intrinsic to the primer extension method used for detection of RNase H cleavage sites and potential artifacts arising from the sequence dependence of the activity of both RNase H and ribozymes+ Another experimental approach for mapping RNA accessible sites utilizes arrays of oligonucleotides of different length that are complementary to the targeted RNA (Milner et al+, 1997;Mir & Southern, 1999)+ This method identifies those oligonucleotides that form stable hybrids with the target RNA from the sets of target-specific oligonucleotides, but the custom design of such arrays (Southern et al+, 1994) restricts wide acceptance of this method+…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments to measure the effect of different single-stranded nucleic acid structures, under high salt conditions, on the rate of duplex formation on solid supports, have shown that RNA or cDNA structural motifs may impede hybridization between probe and target and, therefore, bias the results obtained in gene expression arrays (49)(50)(51)(52). Here, we have reversed the argument and, by taking advantage of the solid support hybridization techniques, we have aimed at evaluating the structural degree of long RNA molecules with potential application to HCV diagnostics and therapeutics.…”
Section: Resultsmentioning
confidence: 99%
“…Much of the pioneering work can be linked to the use of nitrocellulose membranes [69], dot-blots [84] and Southern blots [162]. Development of cDNA or oligonucleotide arrays was possible by combined innovations in micro-engineering, molecular biology [33,120,123,156,163,164] and bioinformatics [59]. The real breakthrough in microarray technology was initiated by two key innovations: the use of non-porous solid supports (such as glass and silicon) and the development of methods for highdensity synthesis of oligonucleotides directly onto the microarray surface [59].…”
mentioning
confidence: 99%